Sobre as diferenças de aplicação entre SVD e PCA: Um estudo pragmático - Silva, Nicollas; Neves, Alan; Rocha, Leonardo; Mourão, Fernando (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2015)
Despite the popularity of SVD and PCA, several applied studies struggle to understand and diferentiate such methods. Frequently, both methods are applied without an adequate assessment about each one is the most appropriate for each scenario. In order to ease the choice between such methods in computational tasks, we conducted a pragmatic discussion that correlates the success of each application to characteristics of each evaluated domain. In this sense, we proposed a methodology that, when applied to three real collections related to distinct tasks, showed that there are diferences in the application of SVD and PCA and that a not elaborate choice may be harmful to the task performed.